L’artifice fait rire, a moins qu’il ne fasse pleurer - Jean-Jacques Lecercle (Sillages Critiques)
The essay starts from the romantic attempt at a poetry of nature devoid of artifice. It shows that any form of art is the result of the artialisation of nature (Alain Roger). It envisages a number of constraints as constitutive of the artifice of comic texts : traducson (D'Antin), psychotyping (Jennings), the productions of fous littéraires, lipogram (Perec), metafiction (Abish). The essay concludes on Barthes's account of the "machinery of meaning" and his concept of neutre.